PENGARUH BIMBINGAN BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL USBN MATA PELAJARAN EKONOMI KELAS XII IPS MAN KUBU RAYA - Suhandis, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
ABSTRACTThe purpose of this research is to get an idea of how much influence tutoring programmed by the school board and the motivation to learn what is being done mentors, so that lessons can be run effectively and efficiently every year in order to deal with the Exam National Standard School (USBN). The research is ex post facto study with explanatory research design. Data collection techniques, namely questionnaires and documentation, as well as data analysis using multiple linear regression.The test showed partial regression coefficient value of partial tutoring of 58 %, which means there is an influence given to the results of Test tutoring National Standard School economic subjects, while 42 % are influenced other factors beyond the variable of the study.The value of the partial regression coefficient of motivation to learn as much as 16.42 %, which means that the contribution of motivation on the results of the National Standard School Test economic subjects, while 83.58 % are influenced by other outside the variable of the study. The result is no effect simultaneously from the adjusted R-square test was found to be 77.4 %, while the remaining 22.6 % is the influence of other variable not examined.Keywords: Tutoring, Motivation To Learn And Test Of The National Standard (USBN)